Quantum chemical study of end-capped acceptor and bridge on triphenyl diamine based molecules to enhance the optoelectronic properties of organic solar cells. (6th April 2022) - Jaffar, Kinza; Elqahtani, Zainab Mufarreh; Afzal, Qaba Qusain; Ans, Muhammad; Riaz, Saima; Tahir, Muhammad Asif; Iqbal, Javed; Mahmoud, Zakaria M.M.; Alrowaili, Z.A.; Al-Buriahi, M.S.
Abstract: This research project focuses on quantum chemical study of triphenyl diamine based molecules and DFT analysis of reference XSln847 and nine designed molecules to boost the efficiencies of organic solar cells and to make viable competitive solar cell. To study photovoltaic features, computational DFT and TD-DFT simulations are used to conduct extensive research at the molecular level of the investigated compounds. CAM-B3LYP/6-31G (d, p) level has been used to perceive molecules analytically for their predicted values of absorption maximum, highest light harvesting efficiency, frontier molecular orbitals and quantum chemical parameters i.e. chemical potential, chemical softness, chemical hardness, and electrophilicity index. Amongst TPDM-1 to TPDM-9 structures, TPDM-9 shows maximum absorption (530 nm) and lowest bandgap (3.19 eV). TPDM-7 has highest power conversion efficiency. While TPDM-4 shows better light harvesting efficiency to enhance organic solar cells efficiency. After successfully verifying the compatibility of the donor and acceptor interfaces, the PTB7-Th (donor) is used for electrophilic designed molecules while for donor designed molecules PC16BM (acceptor) is used as their HOMO LUMO values for the estimation of Voc values. All the proposed molecules show computationally amplified metrics, which is a compelling argument for their potential experimental use in creating effective solar cells. Graphical abstract: Image 1 Highlights: CAM-B3LYP/6-31G (d, p) level has been used to investigate the optoelectronic properties of all molecules. A maximum Absorption wavelength of 530 nm has been found for the TPDM-9 molecule. Narrow bandgap 3.19 eV has been observed for the TPDM-9 molecule.